2011
DOI: 10.1007/s00216-011-5255-1
|View full text |Cite
|
Sign up to set email alerts
|

Surface-assisted laser desorption/ionization-mass spectrometry using TiO2-coated steel targets for the analysis of small molecules

Abstract: Matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS) measurements in the low-molecular mass region, ranging from 0 to 1000 Daltons are very often difficult to perform because of signal interferences originating from matrix ions. In order to overcome this problem, a stainless steel target was coated with a homogeneous titanium dioxide layer. The layer obtained was further investigated for its ability to desorb small molecules, e.g. amino acids, sugars, polyethyleneglycol (PEG 200) or extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Sonderegger et al [68] reported a method for analysis of small molecules by using a conventional MALDI steel target coated with a 50-nm TiO 2 layer. The layer without pores or islands was prepared by electron beam evaporation.…”
Section: Nanomaterial-assisted Ldi Methods Developmentmentioning
confidence: 99%
“…Sonderegger et al [68] reported a method for analysis of small molecules by using a conventional MALDI steel target coated with a 50-nm TiO 2 layer. The layer without pores or islands was prepared by electron beam evaporation.…”
Section: Nanomaterial-assisted Ldi Methods Developmentmentioning
confidence: 99%
“…TiO 2 occurs naturally as three polymorphs: anatase, brookite, and rutile, and these have different chemical and physical properties. To date, several SALDI‐MS analyses with TiO 2 substrates have been reported . Kawasaki et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of organic matrices for small molecule (<500 Da) analysis can be limited due to the interference by fragmentation of organic acid matrices upon laser irradiation yielding background signals at low masses [16][17][18]. To overcome this problem, several alternative matrices, such as carbon nanotube [19][20][21], surfactant-mediated matrix [22][23][24], graphene [25,26] and metal oxides [27][28][29][30][31][32] have been investigated. Among the alternatives, metal oxide nanoparticles have attracted great attention due to its high ability of photonabsorption, large surface area, low heat capacity and high stability during the laser irradiation process, resulting in low background signals in MALDI-MS.…”
Section: Introductionmentioning
confidence: 99%